Performance and tenderness of meat-type chicken fed soybean and benniseed based diets supplemented with microbial phytase (2010)
This experiment was designed to investigate the performance and shear-force (tenderness) of meat-type chicken (broiler) fed Soybean Meal (SBM) and Benniseed based diets supplemented with microbial phytase. 168 Arbor acre strain of broiler chicks were used with Phytase activity of5000 units/ g, two levels of phytase inclusion were used in the study (300 and 600 FTU/kg) in a completely randomized design Birds were allotted into six treatments, with four replicates of 7 birds per replicate. Parameters measured include Body Weight Gain (BWG), Feed Intake (FI) and Feed Conversion Ratio (FCR) which were measured weekly. 2 birds/ replicate were sacrificed at the end of 56days trial and birds were eviscerated and split into primal cuts (thigh, breast and drumstick). The boiled primal cuts were used for the Shear-force assessment. At the end of the 56 days, the FI revealed a significant increase in birds fed Benniseed based diet with 300FTU (101.98g/bird/day) compared to birds on SBM (93.23g/bird/day) and birds fed Benniseed based diet also had the best BWG of2212.50 g compared to SBM based diet with 1557.50g both with 300FTU phytase activity. The birds on Benniseed based diets also had a more tender muscle.